Analisis Pendapatan dan Strategi Pemanfaatan Bantuan Pemerintah pada Pembudidaya Ikan Air Tawar Di Distrik Wania Kabupaten Mimika - Tiodor Marpaung; Mesak Iek (Universitas Cenderawasih, 2025)
The objectives of this study were to analyze the income level of freshwater fish farmer groups receiving government assistance in Wania District, Mimika Regency, and to analyze the strategy for utilizing assistance for freshwater fish farmers in the area. The research method used was descriptive method with quantitative and qualitative approaches. Data collection techniques included observation, questionnaires, and documentation. The research population consisted of 55 freshwater fish farmers, with a sample of 36 respondents calculated using the Slovin formula at a 10 percent error margin. Data analysis was conducted using two methods: income level analysis using the profit formula (TR minus TC) and SWOT analysis to formulate assistance utilization strategies. The results showed that the average gross income obtained by farmers per harvest was IDR 14,570,139, the average total cost incurred was IDR 5,073,611, thus the average net income of freshwater fish farmer groups in Mimika Regency was IDR 9,496,528. The SWOT analysis results indicated that the assistance utilization strategy was in Quadrant I, namely the SO (Strengths-Opportunities) strategy with coordinates (2.831; 2.838). The main strategy to be implemented is to utilize internal strengths to seize external opportunities aggressively. The strategies that need to be maintained include optimizing existing resources by utilizing government assistance, increasing fish production due to the relatively high selling value, ensuring the availability of adequate quality of broodstock and fish seeds, and optimizing training and information on the development of fisheries technology. Keywords: Fish farmers, income, SWOT analysis, government assistance, Mimika Regency